The effect of functional and supportive classic strength trainings in basketball players on aerobic strength, dynamic balance and body composition - Ali Türker; Oğuzhan Yüksel (IP Iermakov S.S., 2021)
Background and Study Aim. It has been aimed to investigate the effects of functional and supportive classic strength trainings in basketball players on aerobic strength, dynamic balance and body composition. Material and Methods. In the study, the test group has performed functional + supportive classic strength training (n=15; 20, 8 ± 1,7 year) three days in a week for eight weeks. Within the process, test and control groups have also continued basketball technical tactics trainings two days in a week. The control group (n=15; 21, 06 ± 1,9 year) has not performed any strength training. The participants have been tested in terms of height, body weight, skinfold calipers, watt bike pro ramp aerobic capacity test and libra see saw balancing board test. When identifying the percentage of body fat, lunge formula has been used. The data has been evaluated with Repetitive Measurements Anova Test. Results. In comparing the group x time interaction, while the developmental difference in the values of VO2max Estimate (mg/kg/min), MET, the percentage of body fat and Left foot lateral balance test has been found out statistically substantial in test and control groups, no significant difference in lateral balance on both feet, right foot lateral balance the measurements and transfer balance measurements on both feet has been found out. Conclusions. As a consequence, it has been seen that functional and supportive strength trainings have contributed to the percentage of body fat, aerobic capacity and dynamic balance. In the planning of yearly training it has been seen that functional strength trainings in preparation phase will contribute to the development levels of basketball players.